GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 2821 species occurrences available in GBIF matching the query: HasCoordinate: true TaxonKey: Acacia auriculiformis Benth. HasGeospatialIssue: false. The dataset includes 2821 records from 48 constituent datasets: 2 records from CONN. 1 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 2 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 7 records from USF Herbarium. 27 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 2 records from Herbier du Bénin. 1 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 2 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 22 records from Ecology, structure and dynamics of private plantations of Teck (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 3 records from Systematic census of the private plantations of the firewood of the Benin .. 1 records from Census of secondary forest of Itchèdè-Toffo (Southern Benin). 3 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 5 records from Herbarium of Taiwan Forestry Research Institute. 2 records from Inventory of Niaouli forest (South-Benin). 13 records from Bernice P. Bishop Museum. 2 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 17 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 1 records from Geneva Herbarium – General Collection (G). 4 records from The digitization of plant specimens of NTU. 5 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 4 records from Distribution de quelques espèces de plantes agroforestières et médicinales au Bénin. 49 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 5 records from PlutoF platform observations. 853 records from Australia's Virtual Herbarium. 1 records from Herbier National de Guinée (HNG). 1 records from Herbarium togoense. 1 records from Census in Agrimey forest reserve (southern Benin). 4 records from ASE - Herbário da Universidade Federal de Sergipe. 2 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 1 records from Data mobilized by the National Herbarium of Benin in the framework of the JRS Biodiversity project of Benin. 8 records from Tropicos Specimen Data. 86 records from "Répertoire des Forêts sacrées dans les Départements de l’Ouémé t du Plateau. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 2 records from Actualización e incremento de la base de datos del Herbario de la Benemérita Universidad Autónoma de Puebla. 4 records from Census of medicinal plants of Benin.. 7 records from Medicinial plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 2 records from Actualización de las bases de datos del Herbario XAL. Fase III. 4 records from Census of the flora of Benin. 1375 records from Flora Atlas N.T.. 2 records from Etapa final de la captura y catalogación del Herbario del Instituto de Ecología, AC, Centro Regional del Bajío. 2 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 2 records from University of Ghana - Ghana Herbarium. 4 records from Institute of Ecology and Evolutionary Biology, National Taiwan University. 137 records from Plants of Papua New Guinea. 1 records from Herbario Amazónico Colombiano. 4 records from NMNH Extant Specimen and Observation Records. 133 records from The census of national forest of Benin .. 1 records from Université Pédagogique Nationale de Kinshasa (UPN) - Données botaniques (2011)- Projet CABIN. 4 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences